Kebun Bibit Mandiri Penunjang Peremajaan Jambu Mete Dalam Meningkatkan Produksi Jambu Mete Di Desa Salut, Kecamatan Kayangan, Kabupaten Lombok Utara - Retno Asih; Aji Hermawan; Sugeng Heri Suseno; Danang Aria Nugroho; Emy Mupid; Maulana Ishak; Yonvitner Yonvitner; Syamsul Bahri Agus (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2019)
The Indonesian government through Pelita II (Five-Year Development) has carried out cashew cultivation projects in the eastern part of Indonesia. This project was carried out in two stages, namely in the 1970s and 1980s, which meant that the average age of cashew plants in Indonesia reached 28-38 years. This age has passed the peak production period so that without intensive care, naturally the production of cashew in Indonesia has decreased. Rejuvenation is an effort to overcome cashew plants whose production begins to decline. The condition of damaged or non-producing gardens needs to be replaced with new, better plants. After the absence of a project from the government, the community tends to use careless seeds that are unclear in their origins and this has the potential to produce plants that are not producing well. The SLAK program (field station for creative agro) from LPPM IPB invites the community to start breeding independently. This business began with the identification of cashew conditions in Salut, then counseling on nurseries and making cashew nursery demonstration plots.